Weight loss in women with hyperemesis gravidarum admitted in a tertiary hospital - Kabir, Shikha; Basher, Md Shahidul; Latif, Tanzina; Akhter, SM Nahida; Nahar, Lutfun; Shaon, Simla Aftab (Bangladesh Medical Journal Khulna, 2018)
Background: Hyperemesis gravidarum is the most severe form of nausea and vomiting in pregnancy with poor pregnancy outcome. Hormonal, psychological, immunological, and infection with H. pylori contribute to the condition. Objective: To estimate the weight loss in women with Hyperemesis gravidarum. Methods: A descriptive, cross sectional study was carried out at antenatal ward, Mymensingh Medical College Hospital, Mymensingh for a period of twenty one months among purposively selected thirty-six patients with hyperemesis gravidarum admitted into the hospital. Results: Highest number (16-44.4%) of respondents were in age group 20 to 24 years with a mean of 23.8 ± 4.5 years. Majority 29 (80.6%) of the women had education less than 12 years, whereas as many as 28 (77.8%) women were housewives, and at least 14 (38.9%) women had unplanned pregnancies. An overwhelming majority 29 (80.6%) of women had their pregnancy duration of 8 to 12 weeks with a mean of 10.6 ± 2.4 weeks. Majority 20 (55.6%) of women were pregnant for the first time, while 19 (52.8%) women had duration of illness for 5 to 9 weeks. Mean difference in body weight was 3.9 ± 2.0 Kg. The loss of weight ranged from 3 to 8 kilograms with a mean of 3.9 ± 1.4 Kg. Loss of weight ranged from 5.0 to 16.7 percent with a mean 7.9 ± 2.8 percent. Out of 16 multigravid women, 7 (43.8%) had history of similar condition in their previous pregnancies. Conclusion: First trimester was time of manifestation of the condition. Patient with Hyperemesis gravidarum often presents with vomiting over 10 times a day with dehydration and remarkable loss of body weight. Bang Med J (Khulna) 2017; 50 : 22-25